Analisis Kompetensi Profesional Guru PAUD Kabupaten Siak Provinsi Riau - Febrialismanto Febrialismanto (PG-PAUD Trunojoyo, 2017)
Teachers are the critical success factors of an educational process. Teachers must have competence in educating one of the competencies of teachers is professional competence. Professional competence describes the ability of teachers to master learning materials. The purpose of this study is to analyze the competence of paud teachers who have completed the S1 study located in Siak regency. The method used is quantitative decryption by conducting tests on 36 teachers. From the results of the research can be seen that the indicators included in the low category is Mastering the basic concepts of health and nutrition as a means of development for each field of development of children with a value of 44.44%, understand the ability of children kindergarten in every field of development 43.52%, and understand the progress of children in every field development in kindergarten 49.07%. From the results of this study can be seen that the three indicators are categorized as low compared with other indicators of professional competence.